Hepatitis G virus infection in lymphoma and in blood donors. Issue 9 (September 1998) - Minton, J; Iqbal, A; Eskiturk, A; Irving, W; Davies, J
Abstract : AIMS: To determine whether the recently described flavivirus, hepatitis G virus (HGV), might contribute to the pathogenesis of lymphoma by testing for the presence of HGV RNA in sera from patients attending lymphoma clinics; to compare the incidence of HGV RNA in lymphoma patients with that in normal blood donors; and to look for potential risk factors for HGV infection and for evidence of hepatic disease in the HGV positive patients. METHODS: Sera were examined from 76 patients with lymphoma and 100 blood donors for the presence of HGV RNA using reverse transcriptase polymerase chain reaction (RT-PCR). RESULTS: HGV RNA was detected in 10% of patients' sera, but only in 1% of blood donor samples. HGV infection was found in patients with various different types of lymphoma, including Hodgkin's disease and non-Hodgkin's lymphoma. The majority (75%) of patients who were HGV PCR positive had undergone transfusion, but only 30% of those who were HGV PCR negative had received blood products. In addition, the number of donor exposures per HGV positive patient was approximately twice that of the HGV negative group. CONCLUSIONS: The data suggest (1) that HGV is present in the normal blood donor population; (2) that patients with lymphoma are at risk of acquiring HGV because of their exposure to blood products; and (3) that persistent HGV infection does not appear to cause serious liver disease in these patients.